Early childhood diets in medieval and Post-Medieval Pälkäne, Finland: Insights from stable isotope analysis - Väre, Tiina; Nordfors, Ulla (Elsevier, 2025)
Early childhood nutrition is crucial for long-term health, yet little is known about breastfeeding and weaning practices in medieval and post-medieval Finland. This study investigates early childhood dietary histories of six individuals buried at St. Michael's Church in Palkane (13th-19th centuries CE) using stable isotope ẟ13C and ẟ15N) analyses of dentin collagen from first permanent molars. These isotopic profiles reveal that all individuals were initially breastfed, but the duration and nature of weaning practices varied. Three medieval individuals (13th century) exhibited prolonged breastfeeding periods of approximately two years or more, consistent with broader European medieval norms. In contrast, two post-medieval children (late 18th-early 19th centuries) were weaned significantly earlier, around their first birthday, possibly reflecting social and economic shifts in dietary practices. Evidence of stress markers, such as enamel hypoplasia and isotopic shifts, suggests that weaningrelated malnutrition or disease influenced some individuals' health and survival. Notably, differences in ẟ15N values point to variations in weaning foods compared to average post-weaning diets, with one medieval individual's profile suggesting the possible inclusion of C4 plants, possibly Chenopodium album, in the weaning diet.